2021
DOI: 10.1002/macp.202100186
|View full text |Cite
|
Sign up to set email alerts
|

High Molar Mass Polycarbonate via Dynamic Solution Transcarbonation Using Bis(methyl salicyl) Carbonate, an Activated Carbonate

Abstract: High molar mass polycarbonate is synthesized via a solution transcarbonation of bis(methyl salicyl) carbonate and bisphenol‐A at temperatures between 60 and 160 °C without the removal of the condensate, allowing the incorporation of thermosensitive monomers into polycarbonate. Kinetic and equilibrium studies show that the polymerization is 20–30 times faster at 120 °C compared to 60 °C, whereas the equilibrium Mw increases from 11 × 103 g mol−1 at 120 °C to 16 × 103 g mol−1 at 60 °C. This polycondensation is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…The equilibrium state found for DGO is considerably higher compared to the reaction equilibrium values mentioned (0.1 to 1.0) for typical nonphenolic alcohols used in polyester synthesis, such as ethylene glycol or 1,4-butanediol with terephthalic acid to produce PET or PBT . In similar carbonate polymerization chemistry, advantages in reactivity were also observed for ortho-substituted phenyl groups: in the work of Kamps et al, bis­(methylsalicyl) carbonate showed reactivity benefits over diphenyl carbonate. , The reactivity benefits of DGO can be used to make the polymerization catalyst-free and/or milder and shorter, resulting in better color and fewer side reactions. It also opens up the possibility of polymerizing with less thermally stable diols or performing polymerization in solution.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The equilibrium state found for DGO is considerably higher compared to the reaction equilibrium values mentioned (0.1 to 1.0) for typical nonphenolic alcohols used in polyester synthesis, such as ethylene glycol or 1,4-butanediol with terephthalic acid to produce PET or PBT . In similar carbonate polymerization chemistry, advantages in reactivity were also observed for ortho-substituted phenyl groups: in the work of Kamps et al, bis­(methylsalicyl) carbonate showed reactivity benefits over diphenyl carbonate. , The reactivity benefits of DGO can be used to make the polymerization catalyst-free and/or milder and shorter, resulting in better color and fewer side reactions. It also opens up the possibility of polymerizing with less thermally stable diols or performing polymerization in solution.…”
Section: Resultsmentioning
confidence: 82%
“… 24 In similar carbonate polymerization chemistry, advantages in reactivity were also observed for ortho-substituted phenyl groups: in the work of Kamps et al, bis(methylsalicyl) carbonate showed reactivity benefits over diphenyl carbonate. 25 , 26 The reactivity benefits of DGO can be used to make the polymerization catalyst-free and/or milder and shorter, resulting in better color and fewer side reactions. It also opens up the possibility of polymerizing with less thermally stable diols or performing polymerization in solution.…”
Section: Resultsmentioning
confidence: 99%
“…Polystyrene polymers of five different molar masses (PS1–PS5, Table ) were synthesized (for molar mass distributions, see Figure S1). Additionally, bisphenol-A polycarbonate was synthesized via solution polymerization. , A prepolymer of polycarbonate (PC-prepol) was synthesized and coupled with AM-2OH to obtain a mechanophore-functionalized polycarbonate (see the SI for details). In this polymer, the mechanophore is not necessarily situated in the center of the chain, and in some cases, more than one mechanophore is likely built into the polymer.…”
Section: Resultsmentioning
confidence: 99%
“…11 In particular, bisphenol-A polycarbonate (PC) is one of the most widely used engineering thermoplastics due to its high impact strength, heat resistance and optical transparency. 12,13 However, PC is industrially produced by polycondensation of bisphenol A (2,2-bis(4-hydroxyphenyl)propane, BPA) with phosgene. [14][15][16] Since BPA is a known endocrine disruptor and phosgene is highly toxic and environmentally harmful, [17][18][19][20][21] there is a significant need to evaluate renewable alternatives to BPA and phosgene in the search for a more sustainable future.…”
Section: Introductionmentioning
confidence: 99%